A metal–organic framework approach to engineer mesoporous ZnMnO3/C towards enhanced lithium storage. Issue 4 (31st January 2022) - Hu, Xi; Huang, Qianhong; Zhang, Yuze; Zhong, Hao; Lin, Zhi; Lin, Xiaoming; Zeb, Akif; Xu, Chao; Xu, Xuan
Abstract : A feasible synthetic method is proposed for the construction of ZnMnO3 /C derived from a bimetallic metal–organic framework as a versatile anode material towards lithium storage. Abstract : Bimetal oxides with high theoretical capacities are one of the promising candidates for lithium-ion batteries (LIBs), yet they show lower cycling stability due to the inherent large volume effect and slow transport kinetics during the lithiation/delithiation process. Thus, to address these issues a simple MOF-5 templated strategy was developed to fabricate mesoporous ZnMnO3 /C and to demonstrate it as an advanced anode material for LIBs. ZnMnO3 /C was simply synthesized by solvothermal and subsequent carbonization processes. Benefiting from the electron transfer from carbon to ZnMnO3, the title anode material could efficiently reduce polarization, facilitate Li + transfer, enhance pseudocapacitive storage, and bring about excellent lithium storage performance, including superior reversible capacity, good rate capability, and long-lasting cycling stability. The results of Raman spectroscopy and density functional theory (DFT) calculations confirmed that after compounding with carbon, the band gap of ZnMnO3 decreased, and the adsorption of Li + increased, which enhances the excellent electrochemical performances of ZnMnO3 /C.